DAMPAK PENGGUNAAN MODEL PROBING PROMPTING LEARNING DI SEKOLAH DASAR - Apdoludin, Subhanadri, Nikita Jofa (Jurnal Tunas Pendidikan, 2023)
The problem in this research is the low process and results of science learning in class IV SDN 60/II Muara Bungo. The aim of the research is to improve the process and results of learning science using the probing prompting learning model. This research is a class action research of two cycles. Each cycle consists of four stages, namely planning, implementing, observing and reflecting. The subjects of this study were Class IV students at SDN 60/II Muara Bungo. The research data was collected through qualitative and quantitative data analysis techniques. The research results in cycle I with an average of 83.9% and in cycle II were 91.1% with a very good category. The results of student observations in cycle I with a percentage of 67.7% and cycle II of 85.3%. While classical completeness in cycle I obtained an average value of student learning outcomes of 64.7% increasing to 82.4% in cycle II. It was concluded that the use of the probing prompt learning model could improve the process and results of learning science